2017
DOI: 10.1155/2017/3183076
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Extended-Spectrum Beta-Lactamases-Producing Microorganisms in Patients Admitted at KRRH, Southwestern Uganda

Abstract: The emergence of extended-spectrum beta-lactamase- (ESBL-) producing pathogenic bacteria at Kabale Regional Referral Hospital (KRRH), located in southwestern Uganda, is of great concern: a phenomenon that worries clinicians and other healthcare workers due to the serious threat they pose to patients. This current study aimed at determining the phenotypic detection of ESBL-producing strains of E. coli, Klebsiella sp., and Proteus sp. isolated from clinical specimens and their prevalence in patients admitted at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
34
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 20 publications
15
34
4
Order By: Relevance
“…This may be attributable to the indiscriminate use of these antibiotics in empirical treatment of almost all ailments as well as use of some of these drugs (Cotrimoxazole) for prophylaxis in HIV infected individuals; thus bacteria are almost always exposed to such drugs which have led to resistance. The incidence of ESBL producing gram-negative bacteria dominated by Klebsiella pneumoniae (60%) and Escherichia coli (40%) in this study is in agreement with study findings by Baguma et al, (2017) indicating Klebsiella pneumoniae and Escherichia coli as the most ESBL producing bacteria [11].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This may be attributable to the indiscriminate use of these antibiotics in empirical treatment of almost all ailments as well as use of some of these drugs (Cotrimoxazole) for prophylaxis in HIV infected individuals; thus bacteria are almost always exposed to such drugs which have led to resistance. The incidence of ESBL producing gram-negative bacteria dominated by Klebsiella pneumoniae (60%) and Escherichia coli (40%) in this study is in agreement with study findings by Baguma et al, (2017) indicating Klebsiella pneumoniae and Escherichia coli as the most ESBL producing bacteria [11].…”
Section: Discussionsupporting
confidence: 93%
“…There is a growing concern by Kabale Regional Referral Hospital clinical team about increased catheter related complications and high ESBL producing uropathogens which is a big challenge during patient management [11].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study at Khartoum state hospitals found that ESBL producer was 30.2% among E. coli [26]. A similar observation has been documented elsewhere [17]. For instances, a study from Burkina Faso reported ESBL producers were more often found in E. coli (67.5%) and K. pneumoniae (26%) [8].…”
Section: Discussionsupporting
confidence: 80%
“…Similar results have been reported in Sudan, where E. coli and K. pneumoniae were the most frequent pathogens recovered from urine samples [16]. Likewise, a study in Uganda reported that K. pneumoniae (52%) and E. coli (44%) were the most frequent Gram-negative organisms from patients' clinical specimens [17]. As well, global studies proved that infections caused by Gram-negative bacteria are predominant compared to other pathogens [18,19].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation